A methodological approach for optimum preservation results: The packaging paradigm - Antonis Kanavouras; Frank A. Coutelieris (International Journal of Food Studies)
The food preservation hypothesis as impacted by overall packaging applications is considered in this work. The objective was to devise a decision supportive method for the selection of “just-right” packaging materials, techniques and procedures. For that, food preservation was critically approached in order to identify the optimum outcome at experimental and packaging selection decision-making levels. A mathematically supported and proven knowledge classification, and the establishment of a straightforward coherence mode among the principles of the natural systemic phenomena, were used. The ultimate aim of this work was to justifiably surpass a simple description of packaging according to its measurable specifications, and instead, engage its inherent properties into a cyclic 8-steps-process for eventually understanding its potential to support any particular preservation hypothesis in question. The proposed methodology includes primarily, the consideration of the study hypothesis and, in parallel, the conclusive remarks and claims with respect to the experimental factors involved (properties, parameters, relations and conditions). Considering the experimentally controlled set-ups that a researcher has to expose the food system to and the role of packaging in obtaining its preservation potential, our method supports the experimenters in selecting the experimental conditions under which the preservation hypothesis can be disclaimed and furthermore, it could indicate the way to reduce experimentation research waste.